128k views
1 vote
11(n-3)=-4

this is also for my friend

User Mumayank
by
5.6k points

2 Answers

1 vote

Answer:

Step 1: Simplify both sides of the equation.

11(n−3)=−4

(11)(n)+(11)(−3)=−4(Distribute)

11n+−33=−4

11n−33=−4

Step 2: Add 33 to both sides.

11n−33+33=−4+33

11n=29

Step 3: Divide both sides by 11.

11n

11

=

29

11

n=

29

11

Answer:

n=

29

11

Explanation:

User Kvetis
by
5.2k points
1 vote

Answer:

Explanation:

11(n-3)=-4 this is also for my friend-example-1
User Terry Djony
by
6.0k points